Airflow inside the nasal cavity: treatment planning and diagnosis using CFD - Zuber, Mohammad; Ahmad, Kamarul Arifin (LAP Lambert Academic Publishing, 2014)
Several limitations associated with the conventional diagnostic approach, demands newer methods of evaluation of complicated nasal physiology and prediction of surgical interventions, made necessary on account of defects and diseases associated with the nasal cavity. This book presents the use of a technique based on functional imaging and Computational Fluid Dynamics (CFD) modeling in generating useful data that can be used to determine and diagnose the upper airways condition. This study has the potential to revolutionize the field of medical diagnosis and can provide deeper insight and understanding of nasal anomalies. CFD along with conventional objective measurement devices can be effectively utilized to study the occurrence of revision surgeries. Such a step can be considered as a milestone and the beneficiaries would be the human subjects who would not be subjected to intuition based surgeries any more. This field of 'virtual surgery' can be deemed as the future of medical science in days to come. This book explores the possibility of regularizing the use of CFD as a diagnostic and decision making tool in treatment planning and decision making.